Roles of Key Epigenetic Regulators in the Gene Transcription and Progression of Prostate Cancer - Deng, Tanggang; Xiao, Yugang; Dai, Yi; Xie, Lin; Li, Xiong (Frontiers in Molecular Biosciences, 2021)
Prostate cancer (PCa) is a top-incidence malignancy, and the second most common cause of death amongst American men and the fifth leading cause of cancer death in men around the world. Androgen receptor (AR), the key transcription factor, is critical for the progression of PCa by regulating a series of target genes by androgen stimulation. A number of co-regulators of AR, including co-activators or co-suppressors, have been implicated in AR-mediated gene transcription and PCa progression. Epigenetic regulators, by modifying chromatin integrity and accessibility for transcription regulation without altering DNA sequences, influence the transcriptional activity of AR and further regulate the gene expression of AR target genes in determining cell fate, PCa progression and therapeutic response. In this review, we summarized the structural interaction of AR and epigenetic regulators including histone or DNA methylation, histone acetylation or non-coding RNA, and functional synergy in PCa progression. Importantly, epigenetic regulators have been validated as diagnostic markers and therapeutic targets. A series of epigenetic target drugs have been developed, and have demonstrated the potential to treat PCa alone or in combination with antiandrogens.